Influences of Liquid Viscosity and Relative Velocity on the Head-On Collisions of Immiscible Drops - Jiaqing Chang; Rongchang Xu; Jinsheng Cui; Qiaolin Song; Teng Shen (Energies, 2022)
Many researchers have devoted themselves to the collision processes of binary droplets of the same liquid. However, the liquids used in their study were limited, and the phase diagram of the collision outcome was depicted in terms of the Weber and the non-dimensional impact parameter. In this research, the variety of liquid was broadened, and the phase diagram characterized by the Weber number and the Ohnesorge number for head-on collisions of immiscible drops was provided. First, a ternary flow model of binary collision of immiscible drops in quiescent ambient air was proposed. Second, the three-phase fluid interface was tracked and updated by iterating the VOF (Volume of Fluid) functions. The flow field was also updated with the PISO (Pressure-Implicit with Splitting of Operators) algorithm. Finally, the effects of the impact velocity and the viscosities of the liquids on the deformation degree of droplets were analyzed.